Special Effect Make Up melalui Pendekatan Art Based Learning menggunakan Model Project Based Learning - Nabilla Khansa; Suci Fajrina; Rosta Minawati; Mega Kencana Saliman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Special Effect Make Up (SFX Makeup) learning is one of the fields within artistic makeup studies that possesses a multidimensional character. The learning process is not only oriented toward mastering technical skills but also involves artistic exploration, the use of technology, and the understanding of aesthetic meanings within cultural and performance contexts. This study aims to identify and synthesize various scholarly perspectives related to SFX Makeup learning strategies through the Art-Based Learning approach using the Project-Based Learning model, in order to formulate a more comprehensive conceptual learning framework. The method employed is qualitative descriptive and literature review, involving five relevant scientific articles discussing topics such as artistic makeup design adaptation, the effectiveness of video tutorial media, innovations in web-based learning media, and the aesthetic exploration of makeup in performance art. The synthesis results indicate that SFX Makeup learning is effective when it integrates four main aspects: (1) artistic and symbolic exploration, (2) pedagogical innovation through interactive learning media, (3) utilization of digital technology for independent learning, and (4) understanding of aesthetics and representational functions within performance contexts. The study concludes that the Art-Based Learning approach is highly relevant to SFX Makeup education as it emphasizes processes of creation, exploration, reflection, and appreciation of artistic works. This approach is expected to cultivate learners who are creative, adaptive, aesthetic, and professionally competent in the field of artistic makeup